Development of the FORMOSAT image product operation system - Lee, Yen-Ling; Hsieh, Min-Che (Proceedings of SPIE, the international society for optical engineering, 2025)
The system will integrate image information from multiple FORMOSAT-8 satellites, allowing general users to query historical image data in real-time and store their query information. FORMOSAT-8 images will be provided as products and services through distributors. The system will offer a comprehensive image ordering platform, enabling distributors to order historical images or task satellite imagery products. Distributors can also integrate the image query system with their own platforms via API. The system will also provide high-resolution image tile subscription services. High-resolution satellite images of Taiwan will be regularly uploaded, allowing subscribers to view high-resolution satellite images from different time periods in real-time through WMTS. Subscribers can also integrate these services into their own platforms via API.